Viral Product Consumption as an Expression of Consumer Culture among Generation Z Female Students at UIN Ar-Raniry Banda Aceh - Yani, Aulia Raysa; Fajarni, Suci (Program Studi Sosiologi Agama Fakultas Ushuluddin dan Filsafat, Universitas Islam Negeri Ar-Raniry, Banda Aceh, Indonesia, 2026)
Social media has made viral product consumption increasingly embedded in the everyday lives of Generation Z university students. However, existing research has more often examined consumer behavior through structural variables than students’ interpretations of consumption as a social practice. This study examines consumer culture among Generation Z female students at Universitas Islam Negeri (UIN) Ar-Raniry Banda Aceh by identifying their recurrent consumption patterns, the social, digital, personal, and financial conditions shaping those practices, and the meanings they attach to consumption across campus and digital environments. The study employed a qualitative case study design involving 11 female students selected through purposive sampling. Data were collected through semi-structured in-depth interviews and analyzed thematically through repeated reading, initial coding, cross-participant comparison, category development, and theme refinement. The findings identified fashion, skincare and makeup, and food as the principal categories of viral product consumption. Fashion carried the strongest symbolic value because it was readily displayed and evaluated across campus and digital environments. Skincare and makeup consumption combined concerns about appearance and confidence with assessments of product suitability, whereas food purchases were approached more selectively because of concerns about quality, safety, and delivery risks. Consumption practices were shaped by spontaneous purchasing, peer relationships, repeated social media exposure, influencer recommendations, and family financial support. Participants interpreted consumption as a means of constructing self-image, strengthening confidence, maintaining social acceptance, establishing digital presence, and rewarding themselves in response to academic and social pressures. The study shows that viral product consumption functioned as an everyday symbolic practice shaped by the interaction of digital exposure, campus relationships, and access to financial resources.